2023
DOI: 10.1021/acsnano.3c02452
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Population Heterogeneity in Vesicle-Based Nanomedicines Using Automated, Single Particle Raman Analysis

Catherine Saunders,
James E. J. Foote,
Jonathan P. Wojciechowski
et al.

Abstract: The intrinsic heterogeneity of many nanoformulations is currently challenging to characterize on both the single particle and population level. Therefore, there is great opportunity to develop advanced techniques to describe and understand nanomedicine heterogeneity, which will aid translation to the clinic by informing manufacturing quality control, characterization for regulatory bodies, and connecting nanoformulation properties to clinical outcomes to enable rational design. Here, we present an analytical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We next employed single-particle automated Raman trapping analysis (SPARTA), previously used to establish single-particle variation in synthetic nanoparticles, , to evaluate changes and distributions of polymer amount per particle incorporated in PLNs. The average Raman spectra across all of the single-particle traps (Figure e) show the characteristic PDLLA-AMBS signals (1032 and 1613 cm –1 ) together with the lipid signal (1439 cm –1 ), confirming coassembly of the polymer and lipid on a single-particle level.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We next employed single-particle automated Raman trapping analysis (SPARTA), previously used to establish single-particle variation in synthetic nanoparticles, , to evaluate changes and distributions of polymer amount per particle incorporated in PLNs. The average Raman spectra across all of the single-particle traps (Figure e) show the characteristic PDLLA-AMBS signals (1032 and 1613 cm –1 ) together with the lipid signal (1439 cm –1 ), confirming coassembly of the polymer and lipid on a single-particle level.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The authors successfully demonstrated the advanced capabilities of SPARTA by analyzing different nanoparticle formulations, including liposomes and polymersomes, as well as the functionalization of polystyrene particles. Since its initial demonstration, SPARTA has been used to study a multitude of nanoparticle systems in recent years. Saunders et al adapted SPARTA to distinguish cargo location and loading heterogeneity within nanoparticle populations . They generated a theoretical model and showed a positive, linear correlation between the encapsulating polymer and cargo mass for membrane loading and a much lower cubic relationship for core loading.…”
Section: Imaging Drug Molecule Distribution and Delivery In Cells And...mentioning
confidence: 99%
“…Reprinted with permission from Saunders, C.; Foote, J. E. J.; Wojciechowski, J. P.; Cammack, A.; Pedersen, S. V.; Doutch, J. J.; Barriga, H. M. G.; Holme, M. N.; Penders, J.; Chami, M.; Najer, A.; Stevens, M. M. Revealing Population Heterogeneity in Vesicle-Based Nanomedicines Using Automated, Single Particle Raman Analysis. ACS Nano 2023 , 17 (12), 11713–11728 (ref ). Copyright 2023 American Chemical Society.…”
Section: Imaging Drug Molecule Distribution and Delivery In Cells And...mentioning
confidence: 99%
“…Researchers have employed automated SPARTA to demonstrate that this technology can accurately characterize single-vesicle cargo information and determine whether SEV is loaded with active ingredients. 78 Additionally, another study introduced a high-throughput method for the absolute quantification of liposomal nanomedicine particle size, drug content, drug encapsulation fraction, and particle concentration at the single-particle level using nFCM. 79 Utilizing single-vesicle technology is crucial for producing and evaluating therapeutic EVs, but further studies are still needed to explore its potential fully.…”
Section: Clinical Application Of Sevmentioning
confidence: 99%